Acute responses and solutions to adapt to a hot environment - Low, D. A. (8th International Congress Mountain Sport & Health. Updating Study and Research from Laboratory to Field. 7-8 November 2019, Rovereto (TN) - Italy. Programme and Book of Abstracts, 2019)
Heat stress environments, such as those with a high ambient temperature and/or high relative humidity, impair exercise performance and can be detrimental to health and wellbeing and even fatal, especially in at risk populations, through increased body heat storage and perceptual strain. The increased heat gain from a hot environment requires elevations in heat loss in order to maintain internal body temperature within safe limits and restrain reductions in exercise capacity and/or avoid heat-related illness. Appropriate autonomic nervous system adjustments are critical for cardiovascular and thermoregulatory responses to heat stress to facilitate heat dissipation. Elevations in cutaneous sympathetic sudomotor and vasodilator activities are key responses to heat gain and at the same time, elevations in cardiac output and vascular resistance of non-cutaneous beds ensure the maintenance of arterial blood pressure within safe limits. Such autonomic adjustments to support elevated heat loss in heat stress environments may not be of the magnitude required to balance heat gain, however, especially if the environmental conditions are uncompensable. Given the recent increased scheduling of athletic events in heat stress environments and global climate change there is an increased focus on the efficacy of various interventions that can mitigate the negative effects of heat stress on exercise performance and health and wellbeing. Such interventions are either acute or chronic but the aim of both are to accentuate heat loss and reduce thermoregulatory, cardiovascular and perceptual strain. Acute strategies include the use of pre- or per-cooling techniques, such as ice slurry ingestion, ice garments, localised cold-water immersion or fanning to either lower internal temperature before or limit the elevations in internal temperature as well as perceptual strain during the exercise-heat stress exposure. Chronic strategies include the use of heat acclimation or acclimatization programmes involving regular exposure to heat stress prior to the athletic event, which result in a range of beneficial physiological and perceptual adaptations. The aim of this presentation will be to 1) briefly outline the acute responses to exposure to a hot environment and 2) critically discuss the solutions to mitigate the effects of a hot environment.